ANALISIS DEEP LEARNING PADA KONSEP RANTAI MAKANAN DENGAN MODEL DISCOVERY LEARNING DI SEKOLAH DASAR - Sabila Nanda Sukiwijaya; Machfudzil Asror (TEACHING : Jurnal Inovasi Keguruan dan Ilmu Pendidikan, 2026)
This study was motivated by the uneven understanding of the food chain concept among students despite the implementation of the Discovery Learning model. The objectives of this study were to describe the implementation of the Discovery Learning model, analyze students’ deep learning, and identify the challenges encountered in learning the food chain concept in Grade V at SD Sabilur Rosyad. This study employed a qualitative approach with a descriptive research design. The research subjects consisted of one teacher and 22 fifth-grade students. Data were collected through observation, interviews, and documentation, and were analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. Data validity was ensured through source and technique triangulation. The findings revealed that the implementation of the Discovery Learning model followed six stages: stimulation, problem statement, data collection, data processing, verification, and generalization. The learning process reflected the characteristics of deep learning, namely meaningful learning, mindful learning, and joyful learning. Students were able to understand the relationships among organisms in a food chain through observation, discussion, analysis, and conclusion-drawing activities. The challenges identified included limited instructional time, differences in students’ abilities, unequal levels of student participation, and limited learning media. Based on the findings, it can be concluded that the Discovery Learning model supports deep learning in teaching the food chain concept to fifth-grade students at SD Sabilur Rosyad. ABSTRAK Penelitian ini dilatarbelakangi oleh belum meratanya pemahaman siswa terhadap konsep rantai makanan meskipun pembelajaran telah menggunakan model Discovery Learning. Penelitian ini bertujuan untuk mendeskripsikan penerapan model Discovery Learning, menganalisis pembelajaran mendalam (deep learning) siswa, serta mengidentifikasi kendala yang dihadapi dalam pembelajaran konsep rantai makanan di kelas V SD Sabilur Rosyad. Penelitian ini menggunakan pendekatan kualitatif dengan jenis penelitian deskriptif. Subjek penelitian terdiri atas guru dan 22 siswa kelas V. Data dikumpulkan melalui observasi, wawancara, dan dokumentasi, kemudian dianalisis menggunakan model Miles dan Huberman yang meliputi reduksi data, penyajian data, dan penarikan kesimpulan. Keabsahan data diperoleh melalui triangulasi sumber dan teknik. Hasil penelitian menunjukkan bahwa penerapan model Discovery Learning telah dilaksanakan melalui tahapan stimulation, problem statement, data collection, data processing, verification, dan generalization. Pembelajaran yang berlangsung telah mencerminkan karakteristik deep learning, yaitu meaningful learning, mindful learning, dan joyful learning. Siswa mampu memahami hubungan antarorganisme dalam rantai makanan melalui kegiatan pengamatan, diskusi, analisis, dan penyimpulan konsep. Adapun kendala yang ditemukan meliputi keterbatasan waktu pembelajaran, perbedaan kemampuan siswa, keaktifan siswa yang belum merata, serta keterbatasan media pembelajaran. Berdasarkan hasil penelitian dapat disimpulkan bahwa model Discovery Learning mampu mendukung pembelajaran mendalam pada konsep rantai makanan di kelas V SD Sabilur Rosyad.